An IoT Inventory Before Deployment: A Survey on IoT Protocols, Communication Technologies, Vulnerabilities, Attacks, and Future Research Directions. Issue 123 (December 2022) - Bang, Ankur O.; Rao, Udai Pratap; Visconti, Andrea; Brighente, Alessandro; Conti, Mauro
Abstract: The Internet of Things (IoT) is a pervasive phenomenon in our everyday life, binding and enabling communication between heterogeneous physical devices and the internet. The applications of this technology range from industrial control to medical devices, hence interconnecting a huge number of devices collecting sensitive information. Although this provides a highly dynamic network with extensive capabilities, its widespread adoption and sensitive nature of the collected data open a large number of challenges from a cybersecurity perspective. In this paper, we offer a fresh perspective on the IoT security landscape by providing a full list of reported vulnerabilites. By organizing protocols and vulnerabilities according to the TCP/IP stack, we guide both novice and expert users and developers in gaining a clear overview of the state-of-the-art IoT and its security issues. Furthermore, by discussing open problems and future directions, we think our paper will be helpful to the research community in designing the next generation of secure IoT.